Rheological properties of cassava starch-kaffir lime essential oil film solution: article / Nur Amalina Naimah Hamidon, Prof. Madya Dr. Junaidah Jai and Norasmah Mohammed Manshor - Hamidon, Nur Amalina Naimah; Jai, Junaidah; Mohammed Manshor, Norasmah (2018)
Food packaging from synthetic polymers are not easily degraded which later can cause environmental issues. On the other hand, food products still need protection as these products are easily deteriorated by oxidation and microbial growth. As an alternative to the conventional food packaging, antimicrobial edible film will extend the shelf-life of food and minimize the use of synthetic plastic. The incorporation of kaffir lime essential oil as antimicrobial agent in edible film formulation has not been studied yet. The rheology of the formulation and the thermal properties of the produced film are important in determining the final characteristics of the film. The rheological properties of cassava film solution with different kaffir lime essential oil of 0.0% v/v, 0.2% v/v, 0.6% v/v, 1.0% v/v and 1.4% v/v were studied at temperature range from 45℃ to 85℃ using Anton Paar MCR 300. The analysis of the data concluded that all flow behaviour index of cassava film solution incorporated with kaffir lime essential oil are less than 1.0. Therefore, all the solutions behave as a pseudo plastic or shear thinning polymer. Meanwhile, the effect of the temperature on the viscosity can be deduce as the increase in temperature result in lower viscosity value. Also, from the Arrhenius equation calculation, lowest activation energy was at 662.84 kJ/mol for 1.4% v/v concentration of sample. This imply this sample is the most temperature stable solution among the other four of samples as the lower the activation energy possessed a more stable temperature behaviour.